Heat exposure and physiological changes among cooks in Kubang Kerian, Kelantan - Ismail, Mohd Nizamuddin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
This study aimed to determine the association between area heat exposure levels with the physiological changes that include body core temperature, blood pressure and heart rate of cooks. This cross-sectional study design utilised purposive sampling method to select 24 cooks from cafe's namely Murni, Nurani and food stall outside the Health Campus Universiti Sains Malaysia. For area heat measurement, Wet Bulb Globe Temperature (WBGT) was mounted on a tripod at height of 1.1 m and was placed near the source of heat for 8 hours. For physiological changes measurement, body core temperature, blood pressure, and heart rate were taken three times per day at pre-shift, mid-shift and post-shift. Respondents’ personal information, health history, work description, and symptoms of heat related illness were asked using questionnaire. Four sampling sites had exceeded the permissible threshold WBGT level of 28.0 temperature (p=0.016) and heart rate (p=0.004) between pre-shift and post-shift. There was no significant correlation (p>0.05) between WBGT index with body core temperature at preshift and mid-shift, but there is a marginal significant association for post-shift (p=0.053, r=0.399). Such increase may be attributed by heat exposure. There was no significant association between body core temperature and blood pressure (systolic and diastolic) and with heart rate (p>0.05). For sociodemographic factor, only age showed significant association with the body core temperature. Preventive measures of heat stress at work such as suitable personal clothing and drink more fluid is highly recommended. xiii 0 Celsius. There was a significant different of body core